Mahāyāna Emptiness or « Absolute Nothingness » ? The Ambiguity of Abe Masao’s Role in Buddhist-Christian Understanding / The Ambiguity of Abe Masao’s Role in Buddhist-Christian Understanding - Keenan, John (Théologiques, 2012)
Abe Masao’s contribution to late twentieth-century Buddhist-Christian dialogue was important in opening new avenues of interfaith understanding. However, some clarity in this dialogue was sacrificed when Christian participants were given to believe that they encountered « the Buddhist view » in Abe’s presentations. The present article contends that in significant ways Abe represented only the Kyōto School philosophy that drew on earlier Japanese philosophers of Absolute Nothingness and their appropriation of Zen enlightenment as the locus for all religious understanding, a place where all negation and affirmation are simultaneously affirmed and denied. The present article contends that Abe’s Kyōto School philosophy does not represent the broad classical traditions of Mahāyāna Buddhism, wherein emptiness does not mean absolute nothingness, but the dependent arising of all places and all philosophies.